Sara Rahbar and the Art of Loving Otherwise - (:unkn) unknown (My University, 2021)
Born in Iran and currently working in New York City, Sara Rahbar is a contemporary multimedia artist who gained some acclaim with her Flag series (2006-present), which was inspired by her experiences in the aftermath of 9/11. Many of these works merge Persian fabrics onto the American flag thus expressing her lived history and political views. To shed light on the political nature of Rahbar’s works writ large, I examine a textile from her War series (2009-2013), titled I Want to Shelter You (2013). Against a flat canvas bag, Rahbar attaches large-caliber bullet casings into a heart-shape to point out that war is never about love. Tied to how war proponents used voices of people from the Middle East to promote the War on Terror, it is a commentary on how human rights were used to justify violence. I examine Faith Ringgold’s flag painting, Flag for the Moon (1969), to show how flag imagery has been used previously to protest both war and prejudice. I also connect this painting to the postcolonial phenomenon of the native informant to track a stream of thought that travels from Frantz Fanon through the Black Power movement and continues in postcolonial feminist critiques of the War on Terror. Beyond claiming Rahbar as an American artist, this reading of Rahbar’s work is an intervention in the art world’s unwitting complicity in using Iranian diasporic artists to further Western supremacy.
Keywords: Contemporary Art; Faith Ringgold; Flag for the Moon; I Want to Shelter You; Postcolonial Feminism; Sara Rahbar